Desain dan Implementasi 3D pada Konsep Geometri Bangun Ruang Menggunakan SketchUp - Kholbi, Juliana; Bawarodi, Septiyana; Mariska, Nadia; Aditiya, Aditiya; Sasalia, Putri; Wulan, Endah nawang (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2025)
This research aims to develop 3D-based geometry learning media using the SketchUp application. The method used is the 4D development model, which includes Define, Design, Develop, and Disseminate. However, this research activity is conducted only up to the Development stage, which involves assessment and evaluation of the media by educational experts as well as a small trial with 13 students. The learning media created aims to help students understand the concepts of spatial geometry in a clearer, visual, and interactive way. Survey results indicate that the media using SketchUp is easy for students to use, which can help them better understand the shapes and structures of spatial figures. Additionally, this media is considered capable of increasing interest in learning and encouraging students to be more active in studying mathematics, especially geometry. Based on assessments from experts and student opinions, this learning media is regarded as good, interesting, and effective for aiding in learning. With a three-dimensional display, students can view spatial objects from various angles, allowing for better understanding.